2014
DOI: 10.1097/wno.0000000000000145
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modeling of Optic Chiasmal Compression

Abstract: The simulation results of the macroscopic chiasmal model are in agreement with the limited experimental results available, suggesting that the finite element method is an appropriate tool for analyzing chiasmal compression. Although the microscopic nerve fiber model was unvalidated because of lack of experimental data, it provided useful insights into a possible mechanism of bitemporal hemianopia. Specifically, it showed that the strain difference between crossed and uncrossed nerve fibers may account for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…The biomechanism of OC compression was studied by Wang et al () using finite element modeling of the OC. He demonstrated that a tumor growing below the OC strains the nasal (crossed) fibers more than the temporal (uncrossed) fibers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biomechanism of OC compression was studied by Wang et al () using finite element modeling of the OC. He demonstrated that a tumor growing below the OC strains the nasal (crossed) fibers more than the temporal (uncrossed) fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Authors have attempted to explain the bitemporal hemianopia caused by tumor compression from below the OC. Two hypotheses have been proposed: stretching fibers of the OC (Moon et al, 2011;Kidd, 2014;Wang et al, 2014) and alteration of the OC blood supply (Blunt and Steele, 1956;Bergland, 1969;Dawson, 1958). Nevertheless, some authors have described anastomoses between the superior and inferior pial network (Collette et al, 1956;Bergland, 1969;Wollschlaeger et al, 1971;Kidd, 2014).…”
Section: Extrinsic Blood Supply Of the Ocmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrobulbar optic nerve is supplied primarily by the ophthalmic artery and surrounded by three meningeal layers . Diseases that commonly affect the optic nerve include optic neuritis (which can be secondary to multiple sclerosis) and glaucoma . The most common disease affecting the retrobulbar optic nerve is retrobulbar optic neuritis.…”
Section: Unambiguous Protein Isoforms Identified In Human Optic Nervementioning
confidence: 99%
“…10 Engineering models have also suggested that this pressure gradient may be responsible for creating a bitemporal hemianopia clinically. 11 Progression of visual loss from involvement of the optic chiasm, particularly with compression due to suprasellar lesions, often proceeds in a stereotypical fashion. Initially the superotemporal visual fields are affected followed by the inferotemporal, the inferonasal, and then the superonasal fields.…”
Section: Visual Lossmentioning
confidence: 99%